Some fixed point theorems for fuzzy mappings - Som T.; Mukherjee R.N. (My University, 2025)
In the present work we extend the concept of weakly dissipative multi-valued map of Aubin and Siegel [1] for a fuzzy mapping and derive a fixed point theorem for such a mapping. We also generalize a result of Heilpern [5] on fuzzy contraction mappings for a fuzzy nonexpansive mapping. Further, we extend a theorem of Kirk and Downing [6] on fixed points of a multi-valued mapping for a fuzzy mapping on a metric space. Finally a fixed point theorem for a generalized nonexpansive fuzzy mapping is given which extends a result of Bose and Sahani [3]. © 1989.